2021
DOI: 10.1097/bpo.0000000000001770
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Neck Growth and Remodeling With Free-Gliding Screw Fixation of Slipped Capital Femoral Epiphysis

Abstract: Background: Treatment of stable slipped capital femoral epiphysis (SCFE) most commonly involves in situ fixation with a standard cannulated screw, leading to physeal arrest. Recently, Pega Medical (Laval, Canada) introduced the free-gliding (FG) SCFE screw, which employs a growth-friendly, telescopic design. This study examines femoral neck growth and remodeling over the first 2 postoperative years in stable SCFE treated with FG versus standard screws. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…For instance, the use of unthreaded fixation using the Hansson hook-pin, proximally threaded screws, or growing implants, such as the Pega Medical Free Gliding (FG) screws and Synthes SCFE screws, may encourage more remodeling of the hip, preventing coxa breva following fixation. [33][34][35][36] Previous research has shown that in moderate to severe slips, the incidence of remodeling was 50% following conventional pinning. 37 The extent of improvement in remodeling and its impact on long-term clinical outcomes, with the use of these systems, however, have yet to be fully ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of unthreaded fixation using the Hansson hook-pin, proximally threaded screws, or growing implants, such as the Pega Medical Free Gliding (FG) screws and Synthes SCFE screws, may encourage more remodeling of the hip, preventing coxa breva following fixation. [33][34][35][36] Previous research has shown that in moderate to severe slips, the incidence of remodeling was 50% following conventional pinning. 37 The extent of improvement in remodeling and its impact on long-term clinical outcomes, with the use of these systems, however, have yet to be fully ascertained.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative may be to use fully threaded screws; however, they are associated with less compression in cases of instability. Some surgeons use ‘inverse threaded’ or ‘free-gliding’ screws to prevent growth disorders [ 40 ]. We do not recommend the use of pins because of the risk of complications due to secondary displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, SCFE has been treated by in situ fixation of the femoral head with a single cannulated screw to inhibit further slippage 5 , 6 . In situ fixation with screws can consequentially cause a physeal arrest, which leads to a relative shortening of the femoral neck 7 – 9 and subsequent LLD 4 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results indicate that monitoring for LLD in mild slip may be unnecessary. Moreover, the alternative growth-preserving implant for in situ pinning 5 , 18 , which has been a longstanding interest in treating SCFE, may be unnecessary for mild slips. It seems reasonable to carefully monitor the LLD in patients with moderate slips.…”
Section: Discussionmentioning
confidence: 99%